LINGUISTIC FEATURES OF ENVIROMENTAL DISCOURSE IN THE ERA OF GLOBALIZATION (Uzbekistan Open Conference, 2025)
This research paper examines ecological discourse as a linguistic phenomenon in the context of globalization. The main characteristics of ecological discourse are analyzed, including its value orientation, evaluativity, and metaphorical nature. The study explores lexical and syntactic features of ecological communication, as well as the influence of globalization processes on the formation and development of ecological discourse. National and cultural features of conceptualizing environmental issues in various linguistic traditions are identified. Special attention is given to modern trends in the development of ecological discourse under the conditions of digitalization of the communicative space. The paper also outlines promising research directions in ecolinguistics and the practical application of the obtained results in education, ecological translation, and social communication.